The Effect of Competitive Advantage towards Financial Performance with Good Information Technology Governance as Moderating Variable - Ira Hapsari (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
Bank’s strength competitive advantage value in digital economic era is depend on its digital and online services quality. The higher usage of online service will enhanced the bank’s profit thus will be reflected in its financial performance. This is the main function of Good IT Governance (GITG) to assure the qualified and safe IT implementation in each bank. This research aimed to analyze the effect of competitive advantage toward financial performance by good IT governance as moderating variable. Competitive Advantage was represented by assets utilization capability and financial performance was represented by ROA (Return on Assets). This research studied on 13 listed banks in Indonesian Stock Exchange which annually published their financial reports during 2012-2016 period. 65 Samples obtained by purposive sampling method,and to strength these objectives, a questionnaire was also developed to measured the good IT governance value. Moderating Regression Analysis using absolute difference method used to examined the research model and hypotheses.The result found that CA has positive effect toward while also found that GITG not moderating the causal relationship between CA toward ROA Keywords: CA, Good IT Governance, ROA